The Effect of Kangaroo Mother Care on Fuss and Crying Time in Colicky Infants - Zahra Akbarian Rad; Mohsen HaghShenas Mojaveri; Yadolla Zahed Pasha; Mosa Ahmadpour-Kacho; Afroz Kamkar; Soraya Khafri; Hajar Hossainnia (Iranian Journal of Neonatology, 2015)
Background: Infantile colic is a common complaint in the first few weeks of life. On the other hand, because of its unknown etiology, there is not a specific therapy for this complaint, but various therapeutic options for reducing pain and restlessness of these infants are recommended. Skin to skin contact by Kangaroo Mother Care (KMC) increases in pain threshold and it seems to be a suitable method for the care of these infants. This study was designed to evaluate the effect of KMC on infantile colic. Methods: This case- control study was performed between March 2012 and March 2013. Subjects were 55 infants with exclusive breast fed infant, aged 15-60 days with excessive fuss and crying, referred to Infant and Child Clinic in Ayatollah Rohani Hospital in Babol, north of Iran. Babies whose weights were less than 2500 Grams and with inheritance and clinical diseases excluded from the study. Infants were subjected to KMC at least 2 hours a day. Standard questionnaire and Barr Scale were filled by interview. Data was analyzed by SPSS v.11.5 and T-test, a P- value less than 0.05 considered being significant. Results: The fuss and crying time before the KMC was 2.21±1.54 hours per day and decreased to 1.16±1.3 hours per day after the implementation of KMC. (p=0.001) Conclusions: Kangaroo mother care at home can be used as a simple and safe method for decreasing of cry and fussiness in colicky infants.